Identifying key mental health and improvement factors in hospital administrators working from home using a DEMATEL-based network analysis model - Sheng Shu; Jie Zhu; Wenqing Shi; Yen-Ching Chuang; Yen-Ching Chuang; Yen-Ching Chuang; Chao Liu; Chao Liu; Hongsheng Lu (Frontiers Media S.A., 2024)
PurposeTo identify the key mental health and improvement factors in hospital administrators working from home during COVID-19 normalization prevention and control.MethodsThe survey was conducted from May to June 2023, and the practical experiences of 33 hospital administrators were collected using purposive sampling. The study examined a set of mental health factor systems. The relationship structure between the factors was constructed using the Decision-making Trial and Evaluation Laboratory (DEMATEL) method. Finally, the structure was transformed using the influence weight of each factor via the DEMATEL-based Analytic Network Process.ResultsRegarding influence weight, the key mental health factors of hospital administrators are mainly "lack of coordination," "time management issues," and "work-life imbalances." The influential network relation map shows that improvements can be made by addressing "improper guidelines," "laziness due to being at home," and "job insecurity" because they are the main sources of influence. The reliability level of the results for the network structure and weight was 98.79% (i.e., the gap was 1.12% < 5%).ConclusionThe network analysis model based on DEMATEL proposed in this study can evaluate the mental health factors of hospital administrators during the pandemic period from a multidimensional and multidirectional perspective and may help improve mental health problems and provide suggestions for hospital administrators.